Comparative international studies of election campaign communication: What should happen next?. (August 2019) - Esser, Frank
The article not only identifies important achievements of comparative international research of election campaign communication but also highlights their challenges. Focusing in particular on content analyses, the article finds that comparative studies examine either the messages of the news media (and here, so far, only the reporting of traditional media is considered) or the messages of the candidates (here, their social media channels are preferentially studied). The combination of both, meaning election studies that are devoted to the interplay of traditional and new channels in an international comparison, are extremely rare and should be intensified. It is encouraging that our knowledge of campaign reporting in a country-by-country comparison has increased in recent years because content analyses have increasingly concentrated on an established set of relevant reporting features – as this articles illustrates with many examples. However, more collaborative, internationally linked comparative scholarship is needed, even if the demands placed on researchers further increase as a result.